2018
DOI: 10.1002/aah.10046
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Monitoring of Flavobacterium psychrophilum in Water by Using a Handheld, Field‐Portable Quantitative PCR System

Abstract: Advances in technology are making it easier for rapid field detection of microbes in aquaculture. Specifically, real-time quantitative PCR (qPCR) analysis, which has traditionally been confined to laboratory-based protocols, is now available in a handheld, field-portable system. The feasibility of using the Biomeme handheld qPCR system for rapid (<50 min) on-site detection and monitoring of Flavobacterium psychrophilum from filtered water samples was evaluated. Paired water samples were collected over a 23-d p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
(40 reference statements)
2
38
0
Order By: Relevance
“…River water samples can be used to map the spatial and temporal distribution of infectious agents and potential exposure landscapes of salmon to diseases in a watershed (Hallett and Bartholomew 2006;Richey et al 2018). Advancements in environmental DNA (eDNA) technology are allowing researchers to rapidly determine the presence and abundance (e.g., cells L -1 ) of multiple agents in a single sample in near-real time (Nguyen et al 2018). As costs fall and sensitivity increases, it will become easier to pinpoint hot spots of infectious agents and associate them with environmental variables and/or identify sources.…”
Section: Data Collectionmentioning
confidence: 99%
“…River water samples can be used to map the spatial and temporal distribution of infectious agents and potential exposure landscapes of salmon to diseases in a watershed (Hallett and Bartholomew 2006;Richey et al 2018). Advancements in environmental DNA (eDNA) technology are allowing researchers to rapidly determine the presence and abundance (e.g., cells L -1 ) of multiple agents in a single sample in near-real time (Nguyen et al 2018). As costs fall and sensitivity increases, it will become easier to pinpoint hot spots of infectious agents and associate them with environmental variables and/or identify sources.…”
Section: Data Collectionmentioning
confidence: 99%
“…The two methods identified similar fluctuations in F. psychrophilum DNA throughout the study. This research demonstrated the proof of concept that rapid field qPCR testing can be used to detect and monitor for aquatic microbes, with results comparable to those from laboratory-based qPCR analysis under ideal laboratory testing conditions [5]. …”
Section: Miniaturized Pcrmentioning
confidence: 98%
“…However, all the above methods are lab-based and time consuming, so that the development of rapid and portable devices with more routine throughput screening methods are likely to continue into the immediate future. Recent research related to on-site detection of GM crops include; loop-mediated isothermal amplification (LAMP) (Hardinge et al, 2018;Singh et al, 2019;Loo et al, 2019), LAMP and a lateral flow biosensor (Cheng et al, 2017), PCR and a lateral flow biosensor (Gao et al, 2019), handheld field-portable qPCR systems (Nguyen et al, 2018;Russell et al, 2018), and nanopore sequencing (Fraiture et al, 2018;Russell et al, 2018).…”
Section: Gm Traceabilitymentioning
confidence: 99%